Integrated reporting – a “one-size-fits-all” solution!? - Knoll, Jessica; Feigenbutz, Anna (Managerial Economics, 2015)
In a world of constantly growing streams of information, extensive transparency in public and private environment as well as recent ﬁnancial crises, it seems to be essential to enhance reporting to a higher, more sophisticated level that considers these changes. Especially, the worldwide ﬁnancial crisis showed that a separated view on ﬁnancial and non-ﬁnancial reporting and an orientation on solely short-term information are no longer appropriate for many stakeholders. Integrated Reporting – representing a symbiosis of ﬁnancial and non-ﬁnancial information – might be a solution to satisfy the changing stakeholder needs. In order to establish this idea, the International Integrated Reporting Council (IIRC) was initiated aiming to provide quantitative and qualitative guidance in form of a framework for organizations on how to conduct integrated reporting. One of the main questions that arises within this context is whether IR is “a one size ﬁts all”-solution or if there is a substantial need for sector-speciﬁc requirements. Therefore, this article provides not only a theoretical background on the concept of IR but also shows some results of experiences examining reporting habits of several, cross-sectoral companies participating in the IIRC’s pilot programme. Additionally, general and sector-speciﬁc requirements as well as chances, challenges and a prospect of IR have to be considered. This article analyses if a general framework on IR is sufﬁcient or if there is the necessity to work on sector-speciﬁc requirements.